Elias Cornelius Boudinot : a life on the Cherokee border - Parins, James W. (American Indian lives., 2005)
Elias Cornelius Boudinot provides the first full account of a man who was intimately and prominently involved in the life of the Cherokee Nation in the second half of the nineteenth century and was highly influential in the opening of the former Indian Territory to white settlement and the eventual formation of the state of Oklahoma. Involved in nearly every aspect of social, economic, and political life in Indian Territory, he was ostracized by many Cherokees, some of whom also threatened his life.